Meningkatkan Aktivitas Belajar dan Perkembangan Spiritual Peserta Didik dalam Konteks Pendidikan Agama Kristen melalui Pendekatan Pembelajaran Berbasis Pengalaman - Saap, Sadrakh Wicaksono (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2023)
Abstract: As education focuses on spiritual aspects and Christian values, it is important to look for effective approaches in terms of the learning process that can increase student involvement in the Christian education learning process. This research aims to investigate how an experiential learning approach can be used to increase student engagement in Christian education. Thus, experimental studies to explore the impact of experiential learning approaches on student engagement in Christian education need to be conducted. So it was found that an experience-based approach in increasing student involvement in Christian education was quite effective. The implication of this research is that an experience-based learning approach has the potential to advance the field of Christian religious education by providing meaningful and relevant experiences for students. This research makes an important contribution in the context of Christian religious education by demonstrating the effectiveness of an experience-based learning approach in increasing student engagement and encouraging spiritual growth. However, further research involving a larger sample and considering variations in Christian educational contexts could provide a more comprehensive understanding of the benefits and application of this approach in the context of Christian religious education.Keywords: experiential learning approach, student involvement, Christian religious education, spiritual growth.